1999
DOI: 10.1007/s002709900412
|View full text |Cite
|
Sign up to set email alerts
|

Management of ureteral strictures in renal transplants by antegrade balloon dilatation and temporary internal stenting

Abstract: Balloon dilatation and temporary internal stenting is a useful method for treating transplant ureteral strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Other investigators 1,9,13,14 have observed the same. This difference may be attributed to the ischemic fibrosis, which is the main reason for late stenosis whereas early stenosis may be secondary to mechanical causes such as kinks, edema, blood clots, or a restricting submucosal tunnel.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Other investigators 1,9,13,14 have observed the same. This difference may be attributed to the ischemic fibrosis, which is the main reason for late stenosis whereas early stenosis may be secondary to mechanical causes such as kinks, edema, blood clots, or a restricting submucosal tunnel.…”
Section: Discussionmentioning
confidence: 48%
“…4,5 The development of percutaneous modes of treatment, such as percutaneous nephrostomy and antegrade ureteral stenting, with low complication rates, may offer an appropriate primary and definitive alternative to open surgery. 1,[6][7][8][9][10][11][12][13][14] Percutaneous procedures for obstructive uropathy have been applied in our institution during the last 6 years. 15 We report our results in 15 patients with renal allograft obstructive uropathy who were managed primarily and definitively with percutaneous nephrostomy and prolonged ureteral stenting.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in the majority of cases, chronic rejection has been found to be the underlying cause, with subsequent progressive decline in the remaining renal function over time. Longterm success has been reported with the treatment of ureteric strictures by percutaneous antegrade dilatation using 6-8 mm angioplasty balloon catheter and placement of double J-stenting alone (37). This appears most effective in those presenting early within 3 months of transplantation, when 50% to 75% of strictures occur.…”
Section: Ureteric Obstructionmentioning
confidence: 94%
“…US-guided drainage of fluid collections is often preferred to correct the extrinsic compression they exert on the collecting system. Surgical reconstruction may be required for long or recurrent strictures [37]. …”
Section: Complicationsmentioning
confidence: 99%